Estimation of Genetic Parameters in Pods and Seed Traits of Candidate Plus Trees of Tecomella undulata (SM.) Seem - Meena, Desha; Singh, Anil; Rawal, Charu (Indian Forester, 2015)
Tecomella undulata is an important timber yielding tree species of arid region. The tree is economically valuable due to quality wood production thus also called as 'Marwar teak'. With the objective to determine extent and nature of variations in seed and pod characteristics, thirty seven phenotypically superior genotypes were identified from 20 different locations from six districts of Rajasthan. Considerable variations were observed in all the pod and seed characteristics like 100-seed weight (0.6-1.3g), seed length (16.7-22.2mm), seed width (8.3-9.3mm), number of seeds/pods (60-68), pod length (18.6-26.2 cm) and pod width (9-10.7mm). Among all the genetic parameters studied, the phenotypic and genotypic coefficients of variations were found close to each other with 100-seed weight and pod length exhibiting the higher values. Estimates of broad sense heritability ranged from 55.4% (for seed length) to 78.26 (for pod length), genetic advance as per cent of the mean ranged between 3.78% and 17.7% with seed width giving the lowest value and 100-seed weight giving the highest value. In conclusion, the results revealed the existence of substantial genetic variation, which can be utilized for further tree improvement programmes of this species.